A Report on Rebecca - Johnson, Carol (Analytic Teaching, 2014)
Introduction: The purpose of this study is to determine after a one year program (October to May), the effects of Philosophy for Children on critical thinking skills of a select group of 22 second graders at Saginaw Elementary. These students have had no previous study in Philosophy for Children and met for 170 days, bi-weekly for at least 30-minutes with no more than three sessions missed. It was anticipated there would be a significant positive difference of critical thinking skills of second graders as observed and noted by the teacher, in a recorded journal, prior, during and after the study. The teacher used Rebecca (Reed, 1986) plus the teacher’s manual for the basis of instruction.